Concentration and size distribution of biological particles in school classrooms - Mostafa, Dr. Mona (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Fungal and bacterial aerosol particles concentrations are measured in a school classrooms at two different floors using the 6-stage Andersen impactor as a bioaersol sampler. The average bacterial concentration is higher than the average fungal concentration. The concentrations were 957 and 955 cfu/m3 for bacterial particles at first and second floors, respectively while the fungal particles concentrations were 146 and 235 cfu/m3 at first and second floors, respectively. Most of the biological particles were concentrated at the size range of respirable particles (< 5 Âµm ) that can penetrate into the alveoli and may cause lung diseases. The human activity is a main factor for the production of microbiological particles. Environmental factors play also a role on the fungal growth. Bacterial concentration is almost twice the guide value of WHO while the fungal concentration is underestimation.